SELEÇÃO DE SISTEMAS DE TRATAMENTO DE EFLUENTES DOMÉSTICOS A PARTIR DO EMPREGO COMBINADO DE MODELAGEM DA QUALIDADE DA ÁGUA, TÉCNICA DE OTIMIZAÇÃO E ANÁLISE MULTICRITÉRIO: ESTUDO DE CASO DA BACIA HIDROGRÁFICA DO RIO BENEVENTE - Almeida, Juliana Pereira de (2020)
In Brazil, about 40% of the urban population still does not have adequate service in the sewage sector, which contributes to the increase of pollution by organic matter in the water bodies of domestic effluents. The wastewater treatment, before launching,